The Maintenance of Indonesian in the Linguistic Landscape of Politeknik Negeri Bali - Gede Adistana Wira Saputra; I Made Darma Sucipta; I Putu Ari Utama Irawan; Runi Fazalani (Global Action and Education for Society, 2025)
This study investigates the maintenance of the Indonesian language within the linguistic landscape of Politeknik Negeri Bali by examining the forms, functions, dominance, and linguistic accuracy of public signage across the campus. Employing a descriptive qualitative approach, data were collected through observation, visual documentation, and sign analysis of room nameplates, safety signs, campus service boards, campaign posters, and other informational media. The results indicate that Indonesian strongly dominates official (top-down) signage, reflecting institutional commitment to the national language as the primary medium of communication. In contrast, English appears more frequently in student-produced (bottom-up) signs, particularly for events and promotional activities, creating symbolic competition between languages. The Balinese language is minimally represented in the campus landscape. These findings suggest that Indonesian language maintenance remains robust, yet further reinforcement—such as language standardization and greater integration of local languages—is still needed to support a balanced multilingual environment.